Correlation of Students' Engagement and Mathematical Representation Ability through Realistic Mathematics Education-Based Differentiated Learning - Maulida, Gebrina Rezki; Johar, Rahmah; Khairunnisak, Cut (FKIP Universitas Lampung, 2024)
Students' mathematical representation skills are still low. One of the reasons is that students are less engaged in learning which does not facilitate students' readiness and different learning styles. Therefore, teachers must facilitate students' diversity with learning that relates to students' daily lives. This study aims to determine the correlation between students' engagement and mathematical representation ability through realistic mathematics education-based differentiated learning. The population in this study were all seventh-grade students of School A and School B. A purposive sampling method was employed to choose one class from each School, consisting of 33 students of one class from School A and 31 students of one class from School B. The research method used is quantitative research with the instrument of engagement questionnaire and mathematical representation ability test. Based on the results of the correlation test, it is found that there is a positive correlation between students' engagement and mathematical representation skills at School A and School B, meaning that the higher the student engagement, the better the students' mathematical representation skills. Keywords: differentiated learning, student engagement, student mathematical representation ability, realistic mathematics education.DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1824-1838